POLA ASUH ORANG TUA PADA ANAK PUTUS SEKOLAH KELUARGA BURUH DI KELURAHAN KOLONGAN AKEMBAWI KECAMATAN TAHUNA BARAT - Christiansy Manoppo; Hamdi Gugule; Y. D. A Santie (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2020)
The purpose of this study was to determine the parenting style of children dropping out of school in the family of workers in Kolongan Akembawi, Tahuna Barat sub-district. This study used qualitative research, with techniques such as observation and in-depth interviews, data collection in this study used internal validation and external validation. , dependability and confirmability Sugiyono, 2010. The results show that the parenting style applied in families whose parents work as laborers in the Kolongan Akembawi sub-district, Tahuna Barat district, is a combination of authoritarian and permissive. Authoritarian parenting is characterized by the existence of absolute rules from parents that cannot be denied by children, especially in selecting schools for children aged 6-12 years. Permissive parenting is characterized by the behavior of parents who always agree with the wishes of the child, the choice of the child is considered by the parents as a policy in the family.